2019
DOI: 10.1007/s11307-019-01375-w
|View full text |Cite
|
Sign up to set email alerts
|

Semiquantitative Parameters in PSMA-Targeted PET Imaging with [18F]DCFPyL: Impact of Tumor Burden on Normal Organ Uptake

Abstract: Terms of use and reuse: academic research for non-commercial purposes, see here for full terms. http://www.springer.com/gb/openaccess/authors-rights/aam-terms-v1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 27 publications
1
34
0
Order By: Relevance
“…Thus, the affinity of the latter agent would be theoretically 30 fold higher compared to [ 18 F]DCFPyL (or 10 fold higher compared to [ 18 F]PSMA-1007). However, human PSMA-targeted PET imaging is a complex interplay of varying factors including biodistribution, radiotracer accumulation in putative sites of disease, renal excretion or normal variant uptake in benign lesions 90. Thus, it is a matter of debate whether IC50 values derived by cell assays indeed reflect clinical reality 74.…”
Section: Part Ii: Recently Introduced 18f-labeled Radiotracersmentioning
confidence: 99%
“…Thus, the affinity of the latter agent would be theoretically 30 fold higher compared to [ 18 F]DCFPyL (or 10 fold higher compared to [ 18 F]PSMA-1007). However, human PSMA-targeted PET imaging is a complex interplay of varying factors including biodistribution, radiotracer accumulation in putative sites of disease, renal excretion or normal variant uptake in benign lesions 90. Thus, it is a matter of debate whether IC50 values derived by cell assays indeed reflect clinical reality 74.…”
Section: Part Ii: Recently Introduced 18f-labeled Radiotracersmentioning
confidence: 99%
“…Another reason why they apply visual interpretations may be because no validated quantitative measurements for [ 68 Ga]Ga-PSMA-11 PET/CT reconstructions are currently available. The use of EARL recommendations for HT-PSMA and TL-PSMA in this study was chosen because, even though these recommendations are used for [ 18 F]-FDG (FDG), the used method for the total lesion glycolysis (TLG) will give the best impression of in vivo distribution of [ 68 Ga]Ga-PSMA-11 by calculating the fractional tumor activity [ 16 , 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…An explanation Pharmaceutics 2021, 13, 699 2 of 11 can be found in the biodistribution of PSMA-tracer as there is also physiological uptake (and therefore irradiation) in healthy tissue such as the kidneys, liver, salivary glands, intestine, and to a lesser degree in the lacrimal glands, spleen, and prostate [9,12,13]. Some have suggested that competition between the uptake of the radiopharmaceutical in prostate tumor tissue and healthy tissue may influence the biodistribution by inducing a 'steal' phenomenon, resulting in diminished uptake in healthy tissue [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Similar to SSTR-directed imaging, recent studies have also reported variable impact of tumor burden among commonly used PSMA-PET/CT radiopharmaceuticals. Gärtner and coworkers reported decreased renal 68 Ga-PSMA-11 uptake in patients with higher tumor burden, whereas renal 18 F-DCFPyL uptake was not similarly affected [65,66]. Again, such discrepant findings with different radiopharmaceuticals highlight the importance of structured reporting systems for patients with different tumor load, as lesions with moderate to faint uptake may be missed, especially close to a normal organ with exaggerated uptake.…”
Section: Common Pitfalls On Sstr- and Psma-pet/ctmentioning
confidence: 99%